Electrochemical Treatment of Textile Dye Bath Wastewater Using Activated Carbon Cloth Electrodes - Zelal Isik; Bahar Ozbey Unal; Ahmet Karagunduz; Bulent Keskinler; Nadir Dizge (Avicenna Journal of Environmental Health Engineering, 2020)
The performance of electrooxidation (EO) treatment using activated carbon cloth (ACC) electrodes on textile dye bath wastewater was investigated. ACC electrode pairs were used as anode/cathode for EO experiments. The effect of current density (50–150 A/m2 ), operating time (0–90 minutes), and solution pH (6-11) were tested for removal of chemical oxygen demand (COD), color, and chloride, as well as the changes in conductivity. 95.5% COD and color removal efficiencies were obtained at current density (CD) of 100 A/m2 at solution pH of 10 for 90 minutes. Moreover, the chloride concentration decreased from 4254 to 35.5 mg/L and solution conductivity decreased from 160 to 131 mS/cm at the same conditions. Operating cost of the EO process was calculated to be 3.13 US$/m3 for 36 kWh/m3 energy consumption. The results indicated that the EO process with ACC electrodes achieved high pollutant removal from textile dye bath wastewater.